CASO DE DESARROLLO DE UN SISTEMA DE GESTIÓN DE CALIDAD EN LA EMPRESA JEP INGENIERÍA - EDSON ROMARIO PÁEZ AVILA; EVER ÁNGEL FUENTES ROJAS (Revista Ingeniería, Matemáticas y Ciencias de la Información, 2019)
Quality management systems encompass one of the most powerful management tools today, their language has becomeso universal that there are many companies worldwide that today implement standards and guidelines in order to improvetheir processes, be more competitive, achieve the desired results and stay in the market. This article presents the case of thedevelopment of a quality management system under the ISO 9001 standard in JEP Ingeniería, a company dedicated toelectrical engineering, automation and industrial assembly; the objective is to describe the experience, difficulties, challengesfaced, benefits and results obtained. For this, a diagnostic matrix, process characterization sheets, risk matrix based on ISO31010, quality control instruments and engineering, among other techniques, were used. The present is a case study of anorganization that achieved the certification of their product, the improvement of their processes and that is prepared tocontinue to achieve the objectives that has been drawn by the hand of a staff that lives the quality today.